Double cropping and manure management mitigate the environmental impact of a dairy farm under present and future climate. (February 2022) - Castaño-Sánchez, José P.; Karsten, Heather D.; Rotz, C. Alan
Abstract: CONTEXT: Strategies are needed to reduce the environmental impacts of dairy farms, and these may become more important as our climate continues to change. Double cropping small grain and corn silages provides a strategy that can benefit dairy farms in the northeastern U.S. as they adapt to a longer growing season. Subsurface application of manure may also reduce nitrogen (N) and phosphorus (P) losses as the region faces warmer temperatures and greater precipitation. OBJECTIVE: Evaluate whole-farm production, environmental and economic impacts of adopting these strategies on a representative dairy farm in central Pennsylvania under recent historical and projected midcentury climate. METHODS: Farm management strategies were simulated using the Integrated Farm System Model to determine effects on crop yields, feed production, volatile, leaching and denitrification losses of N, sediment erosion, sediment-bound and soluble losses of P, farm-gate life cycle greenhouse gas emissions, fossil energy use, and production costs. RESULTS AND CONCLUSIONS: Double cropping increased and stabilized feed production by providing forage from a winter rye crop with less dependency on the summer crops of corn silage and perennial grasses. Summer crops are susceptible to summer droughts, which are expected to increase in this region due to warmer temperatures and increased evapotranspiration. Double cropping was more beneficial in the midcentury climate due to the projected increase in growing season length. Double cropping and subsurface injection of manure reduced total N losses by 12–18% and total P losses by 16–19%. Double cropping using broadcast manure application had a neutral environmental and economic impact on the farm. Adoption of these strategies provided a feasible adaptation and mitigation approach for future climate by reducing projected increases in soluble P runoff and ammonia emission caused by warmer temperatures and greater precipitation while maintaining and potentially reducing total farm production costs. SIGNIFICANCE: Whole-farm simulation provides a tool for evaluating potential benefits and tradeoffs of novel technologies and strategies as agriculture adapts to changes in climate. Although these results are specific to a dairy farm in central Pennsylvania, they generally apply to dairy farms throughout the Northeast U.S. and climates where similar changes in temperature and precipitation are projected by mid-century. Our analyses suggest that use of a more intensive crop rotation (double cropping winter small grain and corn silage) along with improved manure application technology (subsurface injection) can help mitigate dairy farm environmental impacts now and even more in the future. Graphical abstract: Unlabelled Image Highlights: Strategies needed to reduce the environmental impacts of dairy farms are becoming significant with projected climate change Whole-farm impacts of double cropping and subsurface manure injection were evaluated on a representative dairy farm Double cropping increased and stabilized forage production by providing a winter crop and less dependence on summer crops Subsurface injection of manure reduced soluble phosphorus runoff and ammonia volatilization, reducing total P and N losses Adoption of these strategies can help mitigate dairy farm environmental impacts now and even more in the future